Effect of dietary polyphenols on fructose uptake by human intestinal epithelial (Caco-2) cells. (September 2017) - Andrade, Nelson; Araújo, João R.; Correia-Branco, Ana; Carletti, Jaqueline V.; Martel, Fátima
Highlights: High intake of fructose correlates with metabolic syndrome. Quercetin, apigenin and chrysin inhibit uptake of 14 C-fructose by human intestinal epithelial Caco-2 cells. These compounds markedly decrease the expression of GLUT2 and GLUT5. These compounds appear to interfere with both GLUT2 and GLUT5 activity. These polyphenols might decrease the intestinal absorption of fructose, with beneficial effects on metabolic syndrome. Abstract: Intake of high-fructose products is associated with metabolic syndrome development. We investigated if dietary polyphenols can interfere with fructose absorption by the human intestinal epithelial Caco-2 cell line. Acutely, several polyphenols induced a significant decrease (15–20%) in 14 C-fructose uptake. Chronically, 14 C-fructose uptake was also affected by polyphenols; quercetin, chrysin and apigenin (100 µM) were the most effective (±25% decrease). These compounds (100 µM) appear to interfere with both GLUT2 and GLUT5 activity; accordingly, they caused a very marked decrease in the mRNA expression levels of GLUT2 (≅90%) and GLUT5 (≅75%). The effect of these compounds on 14 C-fructose uptake does not involve interference with PKC, PKA, PI3K and p38 MAPK intracellular signaling pathways. Quercetin, apigenin and chrysin might decrease the intestinal absorption of fructose. Further studies are needed to test for their beneficial effects on metabolic syndrome.